Cyber Law: Protection of Society from Cyber Crime in A Prophetic Perspective - Arum Dwi Arta Setyoningsih; Achmad Miftah Farid (Proceeding International Conference Restructuring and Transforming Law, 2025)
Introduction: The role of law enforcement officers as regulated in Law Number 19 of 2016 concerning Amendments to the ITE Law and Law Number 1 of 2024 concerning the Second Amendment to the ITE Law is crucial in efforts to eradicate cybercrime. Their responsibilities include detection, investigation, prosecution of cybercriminals, as well as prevention and handling of cyberattacks. In addition to positive law in Indonesia, cybercrime can also be viewed from a prophetic law perspective. Method: This study uses a normative or doctrinal method with primary data in the form of literature. This type of research is descriptive in nature which aims to provide a representative picture of cyber law and community protection in prophetic law. The approaches used are philosophical, legislative, and literature approaches. Results and Discussion: From the results of the study, it is understood that cybercrime is a form of crime that has emerged in the modern era. According to the analysis of Islamic law (jinayat), perpetrators of cybercrime can be subject to ta'zir punishment. Ta'zir linguistically means prevention (al-man'u). In sharia terminology, ta'zir is an educational punishment (ta'dib) determined based on sin. The punishment can vary from light to severe according to the level of danger.